Koncepcja oceny bezpieczeństwa strategicznego przedsiębiorstwa - Stabryła, Adam (The Concept of an Assessment of the Company's Strategic Security, 2008)
The paper presents a research approach which is applicable in selecting an effective option of management strategy. This approach is based on the estimation of subjective probability and referring it to the ability of counteracting threats. It corresponds to strategic management which is defined as the company's general condition characterized by the maximum mitigation of the impact of adverse factors on its efficiency and strategic potential (the company's major resources and competences). The paper presents a method of selecting an optimal projection in the conditions of risk.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 340-348